2018
DOI: 10.1002/rcm.8164
|View full text |Cite
|
Sign up to set email alerts
|

Rapid analysis of fentanyls and other novel psychoactive substances in substance use disorder patient urine using paper spray mass spectrometry

Abstract: Paper spray mass spectrometry can reliably identify and quantitate fentanyl analogs and other drugs of abuse in urine. Using paper spray cartridges as collection devices reduces exposure and transportation risks associated with biological fluids. Cartridges preloaded with labeled internal standards can be effective for targeted screening of fentanyl analogs and other drugs of abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…We have previously observed that mannitol, a commonly used street drug cutting agent, 31 demonstrated signal ionization enhancements for fentanyl and analogs in PS‐MS measurements, resulting in different calibration slopes 23 . This was not observed in these studies, evidenced by the nearly identical calibration slopes for fentanyl in pure methanol, versus fentanyl in methanol with 10% (w/w) mannitol.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…We have previously observed that mannitol, a commonly used street drug cutting agent, 31 demonstrated signal ionization enhancements for fentanyl and analogs in PS‐MS measurements, resulting in different calibration slopes 23 . This was not observed in these studies, evidenced by the nearly identical calibration slopes for fentanyl in pure methanol, versus fentanyl in methanol with 10% (w/w) mannitol.…”
Section: Resultsmentioning
confidence: 74%
“…This was not observed in these studies, evidenced by the nearly identical calibration slopes for fentanyl in pure methanol, versus fentanyl in methanol with 10% (w/w) mannitol. This may be a MS source‐dependent phenomenon, as the previous study employed a capillary inlet 23 instead of the Z‐Spray inlet geometry used here. However, as Figure 2 illustrates, even a very high solids loading of the OTC cold medication matrix (see Table S4 for composition) of 5% (w/v) in methanol lead to only a modest 15% reduction in the calibration sensitivity for fentanyl.…”
Section: Resultsmentioning
confidence: 99%
“…There is an increasing need for field analysis of drugs of abuse, most notably in the forensic community. PS MS provides a more sensitive solution to perform road‐side testing for fresh blood collected onto paper, compared to the conventional colorimetric techniques (Su et al, ; Wang et al, ; Espy et al, ; Ma et al, ; Costa et al, ; Domingos et al, ; Teunissen et al, ; Kennedy et al, ; Yang et al, ). PS MS is effective for detecting structurally different small organic compounds (Fig.…”
Section: Direct Analysis Of Molecules In Native Statementioning
confidence: 99%
“…With respect to sensitivity, the use of mass spectrometry is a logical choice for drug testing strategies. Numerous groups have demonstrated low picogram to nanogram level detection limits with PS‐MS for a wide variety of analyte and matrix combinations, such as drugs, pharmaceuticals, and metabolites in blood and urine, various contaminants in foodstuffs, and chemical warfare agents, amongst many others. It is worth again noting that PS‐MS is a direct method, unlike other drug analysis procedures, which often require extraction or enrichment steps.…”
Section: Sensitivity and Quantitative Capabilitiesmentioning
confidence: 99%
“…Novel psychoactive substances, with widely varied toxicities, constantly appear in street drug samples and cannot be easily identified or quantified by currently used rapid screening technologies. To address this shortcoming, PS‐MS may be easily interfaced with a high‐resolution mass spectrometer, such as an Orbitrap or Fourier transform ion cyclotron resonance (FT‐ICR), in combination with MS/MS to allow for nontargeted unknown analysis and more definitive sample characterization. As a result, PS‐MS combines ease of sampling with powerful instrumentation to quickly identify novel substances and metabolites in urine samples, or substances from raw drug samples.…”
Section: Specificity and Non‐targeted Analysesmentioning
confidence: 99%